Comparison of Anti-oxidant Activity of Five Elected Wild Commercial Mushrooms in Four Different Solvents as an Alternative Oxidative Stress Reliever - Shahnaz Salamat; Muhammad Shahid (Journal of Food and Pharmaceutical Sciences, 2019)
Mushroom also known as a lit source of nutritional and therapeutical component so in order toevaluate the usefulness of the Pakistani wild mushroom strains as the possible nutracueticals, adetailedstudy entailing several tests for the determination of anti-oxidant potential was carried out on the electedmushrooms in four different solvents. Strains of Lentinus edodes, Pleurotus ostreatus, Volvariella volvacea,Pleurotus eryngii and Ganoderma lucidum were extracted for this particular purpose in the water, n- butanol,n-hexane and choloroform solvents. Test models including Total Phenolic Content assay, Total FlavonoidContent assay, 2,2-diphenyl-1,1-picrylhydrazyl (DPPH) Scavenging Activity assay and Reducing Powerassay were utilized for carrying out the comparative analysis among the selected mushrooms. The acquiredresults indicated that the extract of Volvariella volvacea and Pleurotus eryngii possess copacetic anti-oxidantpotential and can be utilized as oxidative stress reliever in humans. Furthermore, extraction studies alsoindicated that water is the most suitable solvent for anti-oxidants extraction for these mushrooms. Finding ofthe anti-oxidant potential for elected wild mushrooms contra indicate that these mushrooms can be safelyexploited as a amended natural anti-oxidant in comparison to its synthetic counterpart.